Characteristics and predictors of chronic kidney disease in children with myelomeningocele: a nationwide cohort study - Dogan, Cagla Serpil; Taner, Sevgin; Tiryaki, Betul Durucu; Alaygut, Demet; Ozkayin, Nese; Kara, Aslihan; Caliskan, Salim (Springer, 2024)
Background Myelomeningocele (MMC) is highly prevalent in developing countries, and MMC-related neurogenic bladder is an important cause of childhood chronic kidney disease (CKD). This nationwide study aimed to evaluate demographic and clinical features of pediatric patients with MMC in Turkey and risk factors associated with CKD stage 5.Methods Data from children aged 0-19 years old, living with MMC in 2022, were retrospectively collected from 27 pediatric nephrology centers. Patients > 1 year of age without pre-existing kidney abnormalities were divided into five groups according to eGFR; CKD stages 1-5. Patients on dialysis, kidney transplant recipients, and those with eGFR < 15 ml/min/1.73 m2 but not on kidney replacement therapy at time of study constituted the CKD stage 5 group.Results A total of 911 (57.8% female) patients were enrolled, most of whom were expectantly managed. Stages 1-4 CKD were found in 34.3%, 4.2%, 4.1%, and 2.4%, respectively. CKD stage 5 was observed in 5.3% of patients at median 13 years old (range 2-18 years). Current age, age at first abnormal DMSA scan, moderate-to-severe trabeculated bladder on US and/or VCUG, and VUR history were independent risk factors for development of CKD stage 5 (OR 0.752; 95%; CI 0.658-0.859; p < 0.001; OR 1.187; 95% CI 1.031-1.367; p = 0.017; OR 10.031; 95% CI 2.210-45.544; p = 0.003; OR 2.722; 95% CI 1.215-6.102; p = 0.015, respectively). Only eight CKD stage 5 patients underwent surgery related to a hostile bladder between 1 and 15 years old.Conclusion MMC-related CKD is common in childhood in Turkey. A proactive approach to neurogenic bladder management and early protective surgery in selected cases where conservative treatment has failed should be implemented to prevent progressive kidney failure in the pediatric MMC population in our country.
Keywords: Child; Myelomeningocele; Neurogenic bladder; Predictors; Chronic kidney disease